Phenolic compounds participating in mulberry juice sediment formation during storage - Zou, Bo (Zhejiang University Press, 2017)

(untitled) (J Zhejiang Univ Sci B)
The stability of clarified juice is of great importance in the beverage industry and to consumers. Phenolic compounds are considered to be one of the main factors responsible for sediment formation. The aim of this study is to investigate the changes in the phenolic content in clarified mulberry juice during storage. Hence, separation, identification, quantification, and analysis of the changes in the contents of phenolic compounds, both free and bound forms, in the supernatant and sediments of mulberry juice, were carried out using high performance liquid chromatographic system, equipped with a photo-diode array detector (HPLC-PDA) and HPLC coupled with quadrupole-time of flight mass spectrometric (HPLC-QTOF-MS/MS) techniques. There was an increase in the amount of sediment formed over the period of study. Total phenolic content of supernatant, as well as free phenolic content in the extracts of the precipitate decreased, whereas the bound phenolic content in the sediment increased. Quantitative estimation of individual phenolic compounds indicated high degradation of free anthocyanins in the supernatant and sediment from 938.60 to 2.30 mg/L and 235.60 to 1.74 mg/g, respectively. A decrease in flavonoids in the supernatant was also observed, whereas the contents of bound forms of gallic acid, protocatechuic acid, caffeic acid, and rutin in the sediment increased. Anthocyanins were the most abundant form of phenolics in the sediment, and accounted for 67.2% of total phenolics after 8 weeks of storage. These results revealed that phenolic compounds, particularly anthocyanins, were involved in the formation of sediments in mulberry juice during storage.